INDONESIAN-ENGLISH TRANSLATION METHODS USED BY THE HIGHER TRANSLATION ACHIEVERS OF ENGLISH EDUCATION DEPARTMENT OF UNISMA - Raniya Insra Yunita (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This research aimed to discover translation methods used by the higher translation achievers of English education department of UNISMA in translating academic text. The research design was descriptive qualitative research. The subject of this research was translation students who got an excellent final score in 3rd translation subject and students who have massive practice in translating. In order to identify the translation methods used by the higher translation achievers, a questionnaire and documentation were used as the instruments for collecting data. The instruments are collected through online and offline. The translation methods proposed by Newmark (1988) were used as the framework of this study. The process of data analysis included data reduction, data display, and conclusion drawing and verification. The findings of this study showed the students used four types out of eight translation methods used by the higher translation achievers in translating thesis abstracts. Moreover, faithful and semantic were indicated as the most effective methods determined by the higher translation achievers to translate academic text.Â Keywords:Â translation methods, abstract, higher translation achievers